2013
DOI: 10.1183/09031936.00139513
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options in severe fungal asthma and allergic bronchopulmonary aspergillosis

Abstract: Severe asthma with fungal sensitisation and allergic bronchopulmonary aspergillosis encompass two closely related subgroups of patients with severe allergic asthma. Pulmonary disease is due to pronounced host inflammatory responses to noninvasive subclinical endobronchial infection with filamentous fungi, usually Aspergillus fumigatus. These patients usually do not achieve satisfactory disease control with conventional treatment of severe asthma, i.e. high-dose inhaled corticosteroids and long-acting bronchodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 152 publications
1
66
0
5
Order By: Relevance
“…100 The possible role of antifungal therapy in the treatment of fungal allergic asthma has also been reported. 101 Another study demonstrated that although A. fumigatus is not abundant in the indoor environment, isolation of this species from sputum was related to higher airborne concentrations of the fungus in the homes of asthmatic patients, suggesting that the home environment should also be considered as a source of fungal exposure. 102 Therefore, housing intervention may be necessary for the management of fungal allergen-sensitized severe asthma.…”
Section: Aspergillusmentioning
confidence: 98%
“…100 The possible role of antifungal therapy in the treatment of fungal allergic asthma has also been reported. 101 Another study demonstrated that although A. fumigatus is not abundant in the indoor environment, isolation of this species from sputum was related to higher airborne concentrations of the fungus in the homes of asthmatic patients, suggesting that the home environment should also be considered as a source of fungal exposure. 102 Therefore, housing intervention may be necessary for the management of fungal allergen-sensitized severe asthma.…”
Section: Aspergillusmentioning
confidence: 98%
“…Glucocorticoids are considered the treatment of choice in acute-stage (stage 1) ABPA [10,11], although there are no placebo-controlled trials of corticosteroids in ABPA. However, their effectiveness in ABPA as observed from years of experience is so well established that it might be considered unethical to conduct placebo-controlled trials [1,9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, an industry-sponsored, multicentre attempt at a double-blind, placebo-controlled, randomised trial in cystic fibrosis APBA (NCT00787917) was terminated early due to enrolment and retention issues, almost certainly related to a preposterously unrealistic dose regime (600 mg injected daily for 6 months). Actually, real-world omalizumab dosing in ABPA can be addressed by using a dose calculation resulting in a near-conventional treatment regime [31]. Accordingly, a randomised, double-blind, placebo-controlled omalizumab trial in adult asthmatics with ABPA using a cross-over design and dose regime of 750 mg monthly was recently published, validating the uncontrolled literature: omalizumab works [35].…”
mentioning
confidence: 87%
“…Finally, the success of omalizumab (anti-IgE monoclonal antibody) in improving control of moderate-severe allergic asthma has led to great interest and rapidly increasing usage in ABPA, usually undertaken as a steroid-sparing agent, with virtually unanimous reporting of reduced steroid requirements and exacerbations in published uncontrolled studies [30][31][32][33]. However, a recent Cochrane review rightly concluded that omalizumab use cannot be comfortably recommended in the absence of valid controlled trial data [34].…”
mentioning
confidence: 99%